(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2016)
This article may be seen as a continuation of the debate on Mafia Capitale begun by Nando dalla Chiesa in the second issue of this journal. The aim of the article is to continue the conversation on the importance that the Mafia Capitale trial may have on a theoretical level, rather than on a practical one, for the conceptualizing of the mafia phenomenon in a more contemporary and international context. Starting from dalla Chiesa’s observations, and by analyzing a number of problematic issues concerning the conceptualization of the mafia phenomenon abroad, this article affirms that the Mafia Capitale prosecution strategy may be used to identify typical mafia symptomatology to be shared both in Italy and internationally. Such typing would enable an abandoning of stereotypes concerning the Mafia, i.e. that it is (only) an Italian phenomenon (or at most, Italian and U.S.) which often delay or prevent effective recognition of forms of mafia in other countries.